Numerical Simulation of Solid-liquid Phase Flow in Siphon Axial-flow Pump Unit - GUO Chu (Renmin Zhujiang)
To study the performance of the axial-flow pump when delivering sediment-laden flow,this paper conducts the numerical simulations of the solid-liquid phase flow inside the axial-flowpump unit based on the Euler multiphase flow model, RNG k-ε turbulence model and SIMPLECalgorithm, compares the energy performance and flow state of the unit working with clear water andsediment-containing water under the conditions of 0.8, 1.0 and 1.2 times design flow raterespectively, and discusses the influence rules of diameter and concentration of solid-phasesediment particles on the solid-liquid phase flow inside the unit. The results show that:Compared with the clear water conditions at the same flow rate, both the efficiency and lift ofthe unit operating in sediment-laden water are lower, as well as the flow state in the outletchannel and the guide vane is worse; With the increase of the solid-phase particle diameter,the volume fraction of particles on the impeller blades surface increases gradually, while theuniformity of the particle volume distribution is worse. And the solid-phase particles are mainlyconcentrated near the inlet of blade pressure surface and the wheel rim of suction surface;With the increase of incoming particle concentration, the uniformity of solid-phase particledistribution on the blades surfaces and guide vane surface becomes worse. Solid-phase particlesare mainly distributed near the inlet of blade pressure surface and the wheel rim of suctionsurface, and the flow state at guide vane is worse. The results may provide some reference for theoptimal design of axial-flow pump unit.